The reintroduction of bearded vultures in South Africa: a feasibility analysis - Brink, Christiaan Willem (Percy FitzPatrick Institute of African Ornithology, 2016)
The southern African population of bearded vultures, Gypaetus barbatus, is declining rapidly and plans for windfarm developments within the core of this species' range threaten to accelerate the population's passage to extinction. As an insurance against such a situation a reintroduction has been proposed to establish a second bearded vulture population within their historic South African range. Before such a scheme could occur suitable areas, if present, will first need to be identified and the requirements and best implementation strategy will need to be determined. Therefore, the aims of this study were (1) to identify the most suitable site for such a reintroduction and (2) to provide some insight into the potential outcomes of different release strategies. Habitat modelling and GIS techniques were used to identify potential reintroduction sites, most notably based on the presence of cliffs. Potential reintroduction sites were then compared based on a range of habitat attributes, of which the amount of human settlement and power line density was considered most important. Five potential reintroduction sites were identified with the two highest ranking sites situated mostly within the Eastern Cape Province. Various release strategies ranging from captive breeding prioritization to release prioritization were modelled using stochastic modelling software. Results indicated that straight releases, without any captive breeding support, had a high probability of failure (defined <34 individuals) ranging between 78.3 and 95.7% across different mortality scenarios over a 30 year period. Supplementation from captive breeding reduced this to between 25.5 and 49.8%. Although it is important for mortality rates to be lower at the reintroduced site this study shows that a reintroduction initiative can be valuable even if this is not the case, as a reintroduction initiative can reduce the probability of extinction (one sex remains) of the species in southern Africa after 50 years by approximately 30%. This study concludes that a captive breeding programme is imperative for the success of the reintroduction and is a prudent measure considering the continuing decline of the species. However, a complementary study examining release sites on the ground as well as stakeholder attitudes and the socio-economic impacts of bearded vultures will be required before the reintroduction can be implemented.